Southeast Asian Literature in English: Gender and Political Issues in Laotian, Burmese and Vietnamese Short Stories - Ranwarat Poonsri; Ramita Tuayrakdee (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
In teaching Southeast Asian literature in English in Thailand, a lecturer presented a brief historical background of each country. After lecturing on each country’s literature background, the students were assigned to write the reflection essays on short stories studied in class. Then, a lecturer summarized the issues discussed in class and from students’ reflection essays. This article is resulted from the case study of teaching modern Southeast Asian Literary Works in English at IAC international studies ASEAN-CHINA program, Faculty of Liberal Arts, Thammasat university, Thailand. A lecturer and students discovered gender and political issues in Laotian, Burmese and Vietnamese short stories. Laotian and Vietnamese short stories A Bar at the Edge of Cemetery and The Khaki Coat represent writers’ attitudes towards their communist/socialist government. Laos and Vietnam share social problems such as poverty-famine, economic inequality and class struggle. Additionally, Laotian, Burmese and Vietnamese short stories also portray gender issues such as gender inequality, women’s liberation movements, and the effects of war on women.